2020
DOI: 10.1111/cas.14718
|View full text |Cite
|
Sign up to set email alerts
|

dUTPase inhibition confers susceptibility to a thymidylate synthase inhibitor in DNA‐repair‐defective human cancer cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…5-FU, a typical inhibitor of TS, plays a key role in thymidine synthesis, leading to DNA duplication and cell growth [28]. HCT116/R cells showed the overexpression of TS at both the mRNA and protein levels (Figure 2E-G), which was significantly attenuated by co-treatment with 5-FU and CRE (Figure 3C-G).…”
Section: Discussionmentioning
confidence: 99%
“…5-FU, a typical inhibitor of TS, plays a key role in thymidine synthesis, leading to DNA duplication and cell growth [28]. HCT116/R cells showed the overexpression of TS at both the mRNA and protein levels (Figure 2E-G), which was significantly attenuated by co-treatment with 5-FU and CRE (Figure 3C-G).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dUTPase can be targeted by several molecules that can inhibit dUTPase activity efficiency by competing with substrates at enzyme catalytic sites [28,29]. In the course of cancer treatment, dUTPase normally prevents incorporation of dUTP and 5FU-nucleotide FdUTP into DNA and reduces the effectiveness of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbation of dUTP/dTTP pools is also a direct effect of numerous anti-cancer drugs widely used in the clinic (e.g., fluoropyrimidines against thymidylate synthase) [ 26 ]. Combined use of thymidylate synthase and dUTPase inhibitors is associated with a synergetic effect in killing cancer cells [ 28 ]. A similar increased effect has been observed upon parallel inhibition of UNG and thymidylate synthase [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to basic academic interest, detailed characterization of these proteins may help to develop new cancer therapies and antibacterial treatments [ 23 ]. For example, thymidylate synthase inhibitors, such as 5-fluorouracil (5-FU) or 5-fluorodeoxyuridine (5-FdUrd), are widely used in cancer therapies [ 24 , 25 , 26 ] and the first dUTPase inhibitors are undergoing detailed investigations [ 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Inhibition of uracil DNA glycosylase also sensitizes cancer cells to 5-FdUrd similar to like dUTPase inhibition [ 35 ].…”
Section: Ung Inhibitors and Their Potential Biotechnological Applicationsmentioning
confidence: 99%